The place and role of filed concept as a conceptual bases in the construction of architext textual sphere - Julakidze, katerine (Bulletin of Akaki Tsereteli State University, 2026)
The merging of interdisciplinary and interparadigmatics results further consideration of the structural content analysis of anthropocentrical metaparadigm. It is also closely connected with the problematic concepts like structure and energy. They both – the concept of structure and the concept of energy are related to the problem of architext. It is known that in the construction of architext the field and vector concepts have a major role (Levinson) but at the current stage we are to demonstrate the role of filed concepts in the architext construction process.